Speaking in tongues - Jarmel, Marcia; Schneider, Ken (2010)
Closely following four very different local public-schoolers through an academic year, [the producers] draw on subtle nuances of the kids' stories to illustrate the complex shades and permutations of bilingual schooling. Two children are placed in immersion programs to retain their native tongues while learning English, and the other two are in the reverse situation. Their parents list both familiar and surprising reasons for enrolling their children, but each remains a strong proponent of the programs despite criticism from extended family, friends and a loud chorus of English-only activists. Even while dismissing common barbs, the families must confront unique challenges both humorous and serious.